Significance of continuous medical education of general practitioners about common diseases : iron deficiency anemia - Batinac, Tanja (Array, 2009)
Abstract: Three years long, prospective study was performed in order to evaluate a possible influence of continuing medical education of general practitioners on managing the patients with common diseases such as iron deficiency anemia (IDA). Altogether 1586 patients that were referred to Hematology Outpatient Clinic, University Hospital Center Rijeka, Croatia due to diagnosis of IDA were examined by clinical hematologist during the first visit and follow up period, were questioned by the means of questionnaire and complete laboratory analyzes were performed in order to: evaluate physical condition and laboratory findings, to assess duration of anemia, possible other specialists’ consultation, iron supplementation therapy, and finally, determine the type of anemia present. Initial group of 983 patients was examined during one year period. Following the education campaign the same parameters were analyzed in comparable (final) group of 603 patients during next one year period.